(untitled) (Journal of Global Humanities and Social Sciences, 2025)
As for Ibsen’s later work The Master Builder, most people are paying attention to the expression of ethical themes and the study of characters’ self-consciousness. Since The Wild Duck, his works gradually began to explore characters’ hearts, and many scholars classified it as symbolism. This paper analyzes many intentions in Ibsen’s The Master Builder, and reveals how image, the ontological category of poetics and aesthetics, is applicable to drama.